Meningkatkan Kemampuan Membaca Report Text Melalui Game Pada Siswa Kelas IX C MtsN 1 Bengkalis Tahun Ajaran 2018/2019 - - Sumini (Akademika: Jurnal Keagamaan dan Pendidikan, 2019)
Abstract The study aims to find out the students ability in reading report texts by using games (kokora and puzzle) of the ninth grade students class C at MTsN 1 Bengkalis in the academic year 2018/2019. The research was conducted of the ninth grade students class C at MTsN 1 Bengkalis. There were 36 students. This research is classroom action research through for phases; planning, implementation, observation, and reflection. Learning strategy used games (kokora and puzzle). In data collection technique used observation and test. After the implementation of the games (kokora and puzzle), the improvement can be seen from the average value of the class has risen from the result of the first cycle class average rose to 77,88 and the second cycle increased to 89,13. In the first cycle the percentage of the overall completeness of students increased to 69,4% or 25 out of 36 students, then on the second cycle increased to 91,6% or 33 out of 36 students. Based on these descriptions, it can be concluded that an increase learning achievement of students in reading report text begin cycle I and cycle II. Then the use strategy games (kokora and puzzle) can improve learning outcome in reading report text of the ninth grade students class IX C at MTsN 1 Bengkalis.